Green Fluorescent Protein Tag for Studies of Drug-Induced Translocation of Nucleolar Protein RH-II/Gu. (June 1998) - Valdez, B.C.; Perlaky, L.; Cai, Z.-J.; Henning, D.; Busch, H.
We have constructed a human osteogenic sarcoma cell line, U-2 OS/GFPGu, that expresses nucleolar RNA helicase RH-II/Gu tagged with green fluorescent protein (GFP). The presence of a GFP tag does not inhibit RNA helicase, RNA folding and ATPase activities of RH-II/Gu protein. The derived cell line responds to cytotoxic agents like the parental cell line U-2 OS. In the presence of either actinomycin D or toyocamycin, the GFP-RH-II/Gu fusion protein translocates from the nucleolus to the nucleoplasm in the same way as the translocation of endogenous RH-II/Gu. The druginduced translocation of GFP-RH-II/Gu is easily monitored by direct observation of live cells in vivo. This cell line can be used to screen cytotoxic drugs and to study the mechanisms of drug-induced translocation of RH-II/Gu. The cellular localization of RH-II/Gu during the cell cycle-dependent formation of the nucleolus is readily monitored. Real-time results are obtained more quickly without the disadvantages associated with cell fixation and immunofluorescence-based staining.